An investigation into the psychographics of visitors to homestay Malaysia / Dr. Nor'ain Othman and Salamiah A. Jamal - Othman, Nor'ain; A. Jamal, Salamiah (2011)
The government has initiated, organised and will continuously seek to improve the Malaysian homestay programme. The success in operating this programme will be meaningless if we are unable to attract accurate segments to the destination. Since this special interest tourism depends a lot on the niche market, understanding this specific group of visitors is vital in ensuring effective promotion of the programme. Research on the psychographic of the homestay visitors to the country is very much lacking thus this study aims to fulfil the gap. The main objective of this research is to undertake a quantitative approach in identifying the typology of the homestay visitors based on their psychographics as well as socio demographic. Other objectives include: (i) to explore the psychographics of visitors to the homestay programme; (ii) to determine whether differences exist between members of the resulting segments with respect to their vacation behaviour, environmental attitudes and socio demographic characteristics; (iii) to examine if the environmental attitudes, trip and demographic characteristics discriminate between the resulting segments of homestay visitors.